Determination of Profitability of Coal Mining Companies: the Role of Leverage, Liquidity, and Sales Growth - Ulandari, Sintia; Suhardi; Hidayati, Nur (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This study analyzes the impact of leverage, liquidity, and sales growth on the profitability of coal mining companies listed on the Indonesia Stock Exchange from 2019 to 2024. Leverage variables are measured using the Debt to Equity Ratio (DER) and Debt to Assets Ratio (DAR), while liquidity is measured using the Current Ratio (CR). The results of the study indicate that DER, DAR, and CR have a significant effect on Return on Assets (ROA), which suggests that optimal management of capital structure, funding, and liquidity plays an important role in increasing company profitability. The implications of these findings emphasize that companies need to implement appropriate financial strategies to maximize asset performance and support long-term growth. For further research, it is recommended that the sample coverage be expanded to other industrial sectors, such as technology or services, to test whether the relationship between the variables studied remains consistent in different contexts. In addition, the use of moderating variables, such as company size or level of innovation, can provide deeper insight into the factors that influence profitability. Longer longitudinal analysis and consideration of macroeconomic factors, such as interest rates and inflation, are also recommended to understand the long-term impact of leverage and liquidity on company profitability.